Hoover's War on Gays : Exposing the FBI's "Sex Deviates" Program - Charles, Douglas M. (Book collections on Project MUSE., 2015)
"Based on extensive research of primary sources and relentless FOIA requests, Charles provides the first comprehensive history of J. Edgar Hoover and the FBI's systematic (some would say obsessive) targeting, investigation, and harassment of homosexuals for the half century that began in the1930s. One of Charles's signal achievements is to piece together the procedures, purposes, and contents of Hoover's "Sex Deviate File" encompassing an estimated 99 cubic feet, or more than 330,000 pages, but which was destroyed by the FBI in the late 1970s"--